The oldest (~ 1.9 Ga) metadolerites of the southern Siberian craton: age, petrogenesis, and tectonic setting - Donskaya, T.; Gladkochub, D.; Mazukabzov, A.; Denyszyn, S.; Pisarevskiy, Sergei; Motova, Z.; Demonterova, E. (Elsevier BV, 2018)
Geological, geochronological, and isotope-geochemical studies of the metadolerites of the Angaul complex, widespread in the Urik-Iya graben of the southern Siberian craton, were carried out. The metadolerites forming separate conformal bodies (sills) among the metasandstones of the Ingash Formation were studied in detail. U-Pb zircon (SHRIMP) dating of metadolerites yielded an age of 1913 ± 24 Ma, and U-Pb baddeleyite (ID-TIMS) dating of these rocks yielded an age of 1914.0 ± 1.7 Ma. Thus, the date of 1914 ± 2 Ma can be taken as the most precise age estimate for the studied rocks. The metadolerites of the Angaul complex correspond in chemical composition to the normal-alkaline tholeiitic basalts. Metadolerites are differentiated rocks with mg# of 36 to 58. They show fractionated REE patterns: (La/Yb)n = 1.2-3.5. All metadolerites, independently of their mg# value, have low contents of Nb (1.6-10.2 ppm) and show well-pronounced negative Nb-Ta anomalies in multielement patterns (Nb/Nb* = 0.19-0.54). The metadolerites are characterized by positive eNd(T) values ranging from 0.4 to 5.2, which correlate well with their SiO2 content and mg# value. The isotope-geochemical parameters of the metadolerites of the Angaul complex indicate that fractional crystallization, along with the assimilation of the host rocks (AFC), might have been the main process during the formation of the most differentiated metadolerites. The geochemical characteristics of metadolerites with the maximum mg# values of 57-58 and eNd(T) = 5.2 suggest that the parental mantle source of the metadolerites resulted from mixing of predominant depleted mantle material with the subcontinental-lithosphere material. Intrusion of the dolerites of the Angaul complex, as well as the deposition of the sedimentary strata of the Ingash Group, took place at the Paleoproterozoic stage of intracontinental extension caused by the collapse of the orogen resulted from the collision of the Biryusa block with the Tunguska superterrane in the southern Siberian craton.